2013
DOI: 10.1002/bmc.2916
|View full text |Cite
|
Sign up to set email alerts
|

Development of an LC/MS/MS method in order to determine arctigenin in rat plasma: its application to a pharmacokinetic study

Abstract: In this study, a simple and sensitive LC/MS/MS method was developed and validated for the determination of arctigenin in rat plasma. The MS detection was performed using multiple reaction monitoring at the transitions of m/z 373.2 → 137.3 for arctigenin and m/z 187.1 → 131.0 for psoralen (internal standard) with a Turbo IonSpray electrospray in positive mode. The calibration curves fitted a good linear relationship over the concentration range of 0.2-500 ng/mL. It was found that arctigenin is not stable enough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…1), were the main compounds found in plasma after oral administration of AR in rats (22,23). Although our previous rat single-pass intestinal perfusion study demonstrated that extensive hydrolysis and glucuronidation of AR occurred when it passed through the intestinal epithelium (22), all its available in vivo pharmacokinetic studies by far monitored only the parent compound (24)(25)(26). Therefore, pharmacokinetic studies providing concrete plasma concentration profiles of both AR and its metabolites are essential for the understanding of its in vivo biotransformation.…”
Section: Introductionmentioning
confidence: 99%
“…1), were the main compounds found in plasma after oral administration of AR in rats (22,23). Although our previous rat single-pass intestinal perfusion study demonstrated that extensive hydrolysis and glucuronidation of AR occurred when it passed through the intestinal epithelium (22), all its available in vivo pharmacokinetic studies by far monitored only the parent compound (24)(25)(26). Therefore, pharmacokinetic studies providing concrete plasma concentration profiles of both AR and its metabolites are essential for the understanding of its in vivo biotransformation.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). The 5 phenolic compounds were identified as sweroside 19 , isoliquiritin 20 , cardamonin 21 , riboflavin 22 and arctigenin 23 based on fragmentation patterns. Table 1 provides a description of the mass spectrometry identification data based on reference compounds from published sources.…”
Section: Resultsmentioning
confidence: 99%
“…1). The 5 polyphenol compounds were sweroside [19], isoliquiritin [20], cardamonin [21], ribo avin [22] and arctigenin [23]. Results are based on the fragmentation method.…”
Section: Resultsmentioning
confidence: 99%
“…The characterisation of the identi ed polyphenolic compounds is the main focus of this study. Based on chemical ion peaks and mass patterns acquired by LC-MS/MS and contrasted with previously discovered literature data [19][20][21][22][23], polyphenols were identi ed. The results of predicting the cleavage of compounds using LC-MS/MS data are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%